Regionalization and Higher Education Student Mobility in East Africa: Examination of Opportunities and Challenges from the Ugandan Context - Amutuhaire, Tibelius (Journal of International Students, 2023)
There is an increasing trend toward regionalization as higher education adapts to openness and globalization. In response, East African countries formed networks and partnerships that strengthened business, higher education, student and staff mobility, and research. This is because regionalization is embedded in East Africa’s economy, politics, culture, and social norms. In addition, regionalization is influenced by internationalization and globalization. It promises development opportunities, although challenges are inevitable. This paper examines the contributions of regional student mobility to East Africa’s development. We use neoliberal and world systems theories to illuminate the advantages and disadvantages of regionalizing higher education and explain how partner states can maximize opportunities and minimize challenges. Data was collected through convenience sampling of two hundred international students and two staff members in international students’ offices. Data analysis revealed that the regionalization of East African higher education reflects historical power relations; it has benefits though founded on inequalities.